Media Framing of Illegal Migration and Human Trafficking in the Ethiopian Broadcasting Corporation - Tariku, Tesfaye; Fekede Menuta (ETHIOINQUIRY Journal of Humanities and Social Sciences, 2025)
This study examines how the Ethiopian Broadcasting Corporation (EBC) covers illegal migration and human trafficking. We used qualitative content analysis of news reports spanning January 1 to December 30, 2023. Following a qualitative methodology and exploratory design, we utilized comprehensive sampling to select 58 news stories for analysis. Theoretical frameworks such as agenda-setting and framing theories were applied to interpret and elucidate the findings. The research findings revealed that the dominant frames used were the responsibility frame, humanitarian frame, security frame, economic frame, conflict frame, and sociocultural frame. EBC portrayed illegal migration and human trafficking positively while using a negative tone for emigrants. The term "illegal migrant" describes those leaving Ethiopia, while "refugee" refers to those entering Ethiopia. The EBC consistently uses "illegal" instead of "undocumented" and aligns its reporting with the Ethiopian government's perspectives, raising concerns about adherence to journalism ethics.